Student Digital Literacy Through an Integrated Mobile Augmented Reality STEM Learning Model - Suherlan, Agus; Halida, Ane Nitra (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2024)
Background: In the 21st century, among the learning skills that students need and need is digital literacy skills. This study has two objectives, including to determine students' digital literacy skills in each digital literacy indicator after using the mobile augmented reality integrated STEM learning model, and to find out students' responses to the mobile augmented reality integrated STEM learning model. Methods: this study applied a quantitative approach method with the research population of students in grade XI of SMAN 4 Sukabumi with a sample of class XI 3 as the control class and XI 4 as the experimental class. Sample withdrawal technique In this study, a Quasi experiment research design was used with a non-equivalent control group pattern. The instruments used in this study are in the form of digital literacy questionnaires and student response questionnaires. The digital literacy questionnaire used included 18 statements and the student response questionnaire contained 10 statements. Results: Data analysis technique using t-test (Independent Sample T-test). The results of the calculation of the Independent Sample T-test are 0.00 < 0.05, it can be concluded that Hl is accepted and H₀ is rejected. This means that there are implications of the Mobile Augmented Reality integrated STEM learning model on students' digital literacy. Analysis of student response questionnaire data shows an average score percentage of 82% with the